FINANCIAL HEALTH OF COMPANIES IN MALAYSIA: THE USE OF ALTMAN’S Z-SCORE MODEL - Syazwani ‘Izzati Mohd Fauzi; Mazurina Mohd Ali (International Journal of Accounting, Finance and Business, 2018)
This study aims to determine the level of financial health among non-financial institutions in Malaysia by using Altman’s Z-score model and to evaluate other qualitative factors (i.e. poor top management, senior manager or CEO turnover, the poor role of audit committees, types of ownership structure and the nature of companies) that contribute to the corporate failures. This study also aims to examine and compare the use of Altman’s Z-score model among successful and unsuccessful non-financial institutions in Malaysia. The sample selection covers 201 successful listed companies in Bursa Malaysia for the year 2012. Data are hand-collected from the annual reports and through questionnaires. The findings of this study show that the 201 companies’ performances do not portray a favorable condition because most of these companies have the likelihood to suffer bankruptcy. Also, a survey has been conducted to the companies that were listed as PN17 by Bursa Malaysia. From the questionnaires given, it is found that the poor role of top management shows the higher percentage rate (93.4%) of the respondents agree that this factor contributes to corporate failure compared to other factors. This study has found that the Altman’s Z-score model is more accurate for manufacturing companies as compared to non-manufacturing companies. The relatively small sample size of financial distress companies would limit the generalizability of the findings. Further research could continue by examining the factors that contribute to financial distress companies across countries. The findings of this study can be useful to investors in making investment decisions by concerning on manufacturing and non-manufacturing companies. This paper contributes to the extant literature by demonstrating qualitative factors other than quantitative factors that may lead to the financial distress companies.